2007
DOI: 10.1596/1813-9450-4302
|View full text |Cite
|
Sign up to set email alerts
|

Watching More Than The Discovery Channel : Export Cycles And Diversification In Development

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 13 publications
4
86
2
6
Order By: Relevance
“…This result was supported by those of Pham and Martin (2007) using a crosssectional analysis who found out that about 70 percent of the growth in exports in their sample of 120 exporters and 76 importers was explained by extensive margin growth. The results obtained by Hummels and Klenow (2005) and by Pham and Martin (2007) were in contrast with the results of the time series analyses employed by Brenton and Newfarmer (2007) and Amiti and Freund (2006). Both results showed low rates of extensive margin growth over time suggesting that exporting larger quantities of existing products matter more than exporting a wider set of products.…”
Section: Literature Reviewcontrasting
confidence: 56%
See 1 more Smart Citation
“…This result was supported by those of Pham and Martin (2007) using a crosssectional analysis who found out that about 70 percent of the growth in exports in their sample of 120 exporters and 76 importers was explained by extensive margin growth. The results obtained by Hummels and Klenow (2005) and by Pham and Martin (2007) were in contrast with the results of the time series analyses employed by Brenton and Newfarmer (2007) and Amiti and Freund (2006). Both results showed low rates of extensive margin growth over time suggesting that exporting larger quantities of existing products matter more than exporting a wider set of products.…”
Section: Literature Reviewcontrasting
confidence: 56%
“…In other studies outlining additional benefits of diversification, Agosin (2007) and Hesse (2008) concluded that economies which diversified their export bases also witnessed higher income growth rates, while Lederman and Maloney (2007) showed that export concentration correlates negatively with economic growth. Export diversification has also been found to contribute to export growth especially in low income nations, for instance, Brenton and Newfarmer (2007) found that export diversification accounted for 57% of the total export growth in their study of some African nations.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers (e.g., Evenett and Venables (2002), Hummels and Klenow (2005), Kehoe and Ruhl (2006) or Brenton and Newfarmer (2007)) decompose cross-country export variations into intensive and extensive (new-products or new-markets) margins and study the contribution of these margins in export growth. 2 Digging deeper into the extensive margin, Hausmann and Klinger (2006) proposed a measure of "product proximity" based on the conditional probability that one product is exported given that the other is also exported.…”
Section: Introductionmentioning
confidence: 99%
“…Exports grew at an annual compound rate of 10.9% during this time-span, while imports grew at 12.7%; the base year value was multiplied by almost eight in the case of exports and by 11 in the case of imports. Over the same period, world exports grew at an annual compound rate of 8.6% and imports at 8.5% 10 . As for the trade balance, it has been negative for the majority of years (15 out of the 21 observed), and its value has ranged from 18% to 0.1% of total trade.…”
Section: Methodsmentioning
confidence: 99%